The Impact of Family-Friendly Policies in Denmark and Sweden on Mothers? Career Interruptions Due to Childbirth - Elina Pylkkänen; Nina Smith (Institute for the Study of Labor (IZA), 2004)
We analyze the impact of family-friendly policies on women?s career breaks due to childbirth in Denmark and Sweden. In both countries, the labour force attachment of mothers is high, and more than 90% of the women return to work after childbirth. Sweden and Denmark are culturally similar and share the same type of welfare state ideology, but differ remarkably in pursued family policies. The impact of family policy variables on the probability of returning to the labour market is estimated using a duration model approach. Our results show that economic incentives and leave periods of the fathers affect the behaviour of mothers in both countries. However, family policy instruments are found to have a much larger impact on Swedish mothers? behaviour compared to Danish women. We explain this finding by the fact that family-friendly policies in Sweden have focused much more on flexible leave schemes and on the shared responsibilities of the parents than in Denmark.
Keywords: J22; J1; 330; family-friendly policy; maternal leave; paternal leave; childcare; Familienpolitik; Mutterschutz; Erziehungsurlaub; Frauenerwerbstätigkeit; Berufliche Integration; Schätzung; Vergleich; Schweden; Dänemark